Sharia Financial Literacy in Improving the Efficiency and Sustainability of Small and Medium Enterprises - Dwi; Luthfi Zamakhsyari; Havidz Cahya Pratama (Universitas Muhammadiyah Purwokerto, 2025)
Community service activities were carried out at the Banyumas Regional Leadership of Aisyiyah. Aisyiyah contributes to the Indonesian economy through, among other things, the Aisyiyah Entrepreneurs Association (IPAS) and the Aisyiyah Economic and Employment Council (MEK). The IPAS community is a group of Aisyiyah members who have run businesses and those who will or wish to run businesses. The businesses run can generally still be categorized as MSMEs. MSMEs in Indonesia cannot be separated from the halal industry MSMEs, considering that most MSME businesses are in sectors that fall under the halal industry category. With an awareness of the importance of the MSME sector for the Indonesian economy, strengthening MSMEs has become one of the main strategies of the Indonesian Sharia Economic and Financial Master Plan. Currently, Islamic finance is growing rapidly with many Islamic financial institutions offering financial products and services based on Islamic law. However, the fact is that Islamic finance still has a low market share in Indonesia, a country with a Muslim majority population. Therefore, the level of Islamic financial literacy among MSMEs is important for business efficiency and sustainability.